2021
DOI: 10.5539/hes.v11n3p56
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Instructional Model Based on Creative Problem-Solving Principles with Social Media to Promote the Creation of Educational Innovation for Pre-service Teachers

Abstract: The main research purpose focused on the effects of conducting the instructional model based on the principles of creative problem solving with social media to promote the creation of educational innovation for pre-service teachers. The participants consisted of twelve pre-service teachers. Research instruments were 1) the instructional model based on the principles of creative problem solving with social media, 2) the test of knowledge and creation of educational innovation, 3) the creation of educational inn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…A model for creating innovation is defined as an ID model that includes a systematic teaching and learning plan to provide guidelines for teachers to organize teaching and learning processes based on principles of creative problem-solving, to promote the creation of educational innovation [1]. One of these models was developed by Seechaliao in 2018, based on the principles of creative problem-solving and social media in real-life situations [1]. Implementation of the resulting model revealed that it could effectively promote the creation of educational innovation for pre-service teachers.…”
Section: Models For Creating Innovationsmentioning
confidence: 99%
See 2 more Smart Citations
“…A model for creating innovation is defined as an ID model that includes a systematic teaching and learning plan to provide guidelines for teachers to organize teaching and learning processes based on principles of creative problem-solving, to promote the creation of educational innovation [1]. One of these models was developed by Seechaliao in 2018, based on the principles of creative problem-solving and social media in real-life situations [1]. Implementation of the resulting model revealed that it could effectively promote the creation of educational innovation for pre-service teachers.…”
Section: Models For Creating Innovationsmentioning
confidence: 99%
“…Implementation of the resulting model revealed that it could effectively promote the creation of educational innovation for pre-service teachers. However, social media that is included in the model should be updated continuously in order to select that which is most appropriate for learning activities, students' learning styles, and their behaviors [1].…”
Section: Models For Creating Innovationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Beberapa penelitian tentang model Pembelajaran Pendidikan Agama Islam sudah banyak dilakukan. Diantaranya yang dilakukan oleh (Vereş, 2021), (Lubiano et al, 2021), (Saenab et al, 2021), (Akbulut & Hill, 2020), (Seechaliao & Yurayat, 2021), (Khan & Rana, 2021), (Elizabeth et al, n.d.), namun mereka tidak meneliti tentang ISRA sebagai dasar model dan moderasi beragama. Perbedaan penelitian sebelumnya dengan penelitian ini adalah terletak pada penerapan model ISRA dalam pembelajaran Pendidikan Agama Islam, dengan demikian tujuan penelitian ini adalah untuk menciptakan model pembelajaran PAI dalam bingkai Islam rahmatan lil'alamin.…”
Section: E-issn: 2614-1396unclassified